“Our kids are our future”: Barriers and facilitators to vaccine uptake and timeliness among Aboriginal children younger than five years in Boorloo (Perth), Western Australia - Carla Puca; Paige Wood-Kenney; Naomi Nelson; Jordan Hansen; Judy Mathews; Erin van der Helder; Justin Kickett; Melanie Robinson; Katie Attwell; Anastasia Phillips; Valerie Swift; Christopher C. Blyth; et al. (PLoS ONE, 2025)
Introduction Rates of several vaccine preventable diseases, and associated hospitalisation, are higher among Aboriginal and/or Torres Strait Islander children than non-Indigenous children. Western Australia has among the lowest childhood vaccine coverage in Australia, particularly among Aboriginal and/or Torres Strait Islander children. Delayed vaccination is also more common in this population. This project aimed to understand the barriers and facilitators to vaccine uptake and timeliness among Aboriginal and/or Torres Strait Islander children aged under five years in Boorloo (Perth). Methods The Tailoring Immunisation Programs method was used to determine the barriers and facilitators to vaccination. Between March – November 2023, in-depth interviews were conducted with 18 parents/carers of Aboriginal and/or Torres Strait Islander children in Boorloo who were currently or previously overdue for one or more childhood vaccines. Qualitative data were analysed in NVivo 14 using deductive and inductive coding following the Capability-Opportunity-Motivation-Behaviour model. Results The majority of participants believed vaccines are safe, effective and supported vaccination as a means to strengthen the next generation of Aboriginal and/or Torres Strait Islander children. Barriers to on-time vaccination related to access and ineffective reminder systems. Participants expressed limited knowledge about additional vaccines recommended for Aboriginal and/or Torres Strait Islander children under Australia’s National Immunisation Program. Conclusion An increase in vaccine coverage and timeliness will optimise protection and decrease the burden of disease in Aboriginal and/or Torres Strait Islander children in Boorloo. This can be supported by policy interventions to better cater for the needs of families, including addressing transport challenges, being mindful of the wider network of kin and care relationships, ensuring the funding of Aboriginal health services, and co-designing culturally appropriate resources. The federal government should use the Centrelink system to notify all eligible families of pending vaccines due.